Brain Informatics International Conference, BI 2012, Macau, China, December 4-7, 2012, Proceedings - Zanzotto, Fabio.; Zanzotto, Fabio.; Tsumoto, Shusaku.; Tsumoto, Shusaku.; Taatgen, Niels.; Taatgen, Niels.; Yao, Yiyu Y.; Yao, Yiyu Y. (Lecture Notes in Artificial Intelligence ;, 2012)
This book constitutes the refereed proceedings of the International Conference on Brain Informatics, BI 2012, held in Macau, China, in December 2012. The 34 revised full papers  were carefully reviewed and selected for inclusion in the book. The papers are organized in topical sections  on computer science, information technology, artificial intelligence, web intelligence, cognitive science, neuroscience, medical science, life science, economics, data mining, data and knowledge engineering, intelligent agent technology, human computer interaction, complex systems, and system science.